Mobile Learning of Education Character based on Multicultural Value - Yoyo Zakaria Ansori; Erik Santoso (STAI Hubbulwathan Duri, 2021)
This study aims to provide an understanding of character education based on multicultural values in elementary school students. The method used is quasi-experimental to see the changes that occur after using mobile learning in class VI SDN Kadipaten 1 Majalengka. The population and sample of the study were the sixth-grade students of SDN Kadipaten Majalengka in the 2020/2021 academic year. The data collection technique used a test that was used to determine the student's tolerance attitude. Based on the data processing and analysis results, it can be concluded that the attitude of tolerance needs to be given a good understanding at the level of elementary school students. It is because elementary school students are at a stage where imitation is very high. The